Fermentação e degradabilidade ruminal em bovinos alimentados com resíduos de mandioca e cana-de-açúcar ensilados com polpa cítrica peletizada - Da Silveira, Roselene Nunes [UNESP] (2002)
The objective of this work was to evaluate the dry matter (DM), neutral detergente fiber (NDF) and starch ruminal degradability besides pH, N-NH3 and valatile fatty acids (VFA) in bovines fed diet with corn (CS), cassava meal (CMS), cassava hull (CHS), and sugar cane (SCS). The CMS, CHS and SCS were ensiled with citrus pulp (CPP). Four crossbred, castrated, rumen and duodenum cannulated steers were used in four experimental periods, with 11 days for diet adaptation and 8 days for sampling. The experimental design was 4×4 Latin Square. There were eight incubations times: 3, 6, 12, 24, 48, 72, 96 and 120 hours. The CMS showed higher DM, and NDF effective degradation (Kp 5%) (48.44 and 45.78%, respectively) than CS (45.50, 23.75%), CHS (43.87, 24.20%) and SCS (40.76, 25.78%). For all the treatments, the pH and the ruminal concentration of N-NH3 were appropriate for the growth of the rumen microrganisms. The VFA values of the CS, CMS and CHS treatments were similar among themselves and higher than the SCS treatment.